Transcatheter Closure of Atrial Septal Defects in Children, Middle-Aged Adults, and Older Adults: Failure Rates, Early Complications; and Balloon Sizing Effects. (19th June 2012) - Vijarnsorn, Chodchanok; Durongpisitkul, Kritvikrom; Chanthong, Prakul; Chungsomprasong, Paweena; Soongswang, Jarupim; Loahaprasitiporn, Duangmanee; Nana, Apichart
Abstract : Objectives . To compare the failure ratio and inhospital complications across three age groups of patients and to investigate the effects of balloon sizing on the success and the device diameter. Methods . This retrospective review was of 665 patients who had been listed for transcatheter-based closure of ASD between 1999 and 2010. The patients were divided into three age groups: children (<18 years; n = 183 ), adults (18–50 years; n = 337 ), and older adults (>50 years; n = 145 ). Procedural outcomes and early complications were reviewed. Use of balloon sizing was explored for its benefits. Results . Overall, failure of closure was 6.6% (n = 44 ). Use of balloon sizing tended to lead to a smaller device/defect ratio that was comparable to procedures without balloon sizing, though it did not predict the success rate (OR 1.4, 95% CI 0.7–2.3). Seven patients reported device embolization (1%). No mortalities were noted. In-hospital complications were 3.4%, with common complications, being vascular complications (1.4%) and cardiac arrhythmia (1.1%). No differences in failure rate or events were found among the three groups. Conclusion . Transcather closure of ASD is feasible and safe, regardless of the patient's age. A low rate of early complications was noted. Balloon sizing does not aggravate an oversizing of the device, but does not predict success.